Implementation of Artificial Intelligence in Islamic Religious Education Learning at Madrasah Ibtidaiyah - Mustoip, Sofyan; Al Ghozali, Muhammad Iqbal; Lestari, Diana; Dz, Abdus Salam; Damayanti, Indani; Mehir, Saefudaullah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2024)
This research aims to explore and analyze the implementation of artificial intelligence (AI) in Islamic Religious Education (PAI) learning at Madrasah Ibtidaiyah, with a focus on innovation and the effectiveness of using AI in improving the quality of learning. The research method uses a qualitative approach with a case study design involving five Madrasah Ibtidaiyah in Cirebon Regency, involving in-depth interviews with 15 PAI teachers and 50 students, classroom observations, and document analysis. The research results show that the application of AI provides significant benefits such as delivering more interactive material, personalizing learning according to student needs, and more efficient learning evaluation. In conclusion, the implementation of AI in PAI learning at Madrasah Ibtidaiyah can improve the quality of learning and student understanding, although its success depends on technological readiness, teacher training, and support from related parties. It is hoped that this research will become a reference for other madrasas in adopting AI to increase the effectiveness of PAI learning.